Financial Development and Economic Growth Nexus: A Revisionist Approach. (23rd August 2017) - Nyasha, Sheilla; Odhiambo, Nicholas M.
Abstract : In this piece, we highlight some of the salient issues and controversies surrounding the relationship between financial development and economic growth, from both the theoretical and the empirical fronts. We first discuss the controversies on the role of financial development in economic growth; and we then proceed to review the causal relationship between financial development and economic growth. We conclude that the relationship between financial development and economic growth is highly complex, and is dependent on a number of factors. Hence, the argument that financial development always leads to economic growth should be taken with extreme caution.